Предмет: Алгебра,
автор: Laaaamp
CРОЧНО!
Ответы
Автор ответа:
0
tg=(tg(3π/4)-tg2x)/(1+tg(3π/4)×tg2x)=(1-tg2x)/(1+tg2x)=
=(cos2x-sin2x)/(cos2x+sin2x).(1+сos4x)/tg(3π/4 - 2x)=(2cos^в квадрате 2x)·(cos2x+sin2x)/(cos2x-sin2х)
=(cos2x-sin2x)/(cos2x+sin2x).(1+сos4x)/tg(3π/4 - 2x)=(2cos^в квадрате 2x)·(cos2x+sin2x)/(cos2x-sin2х)
Автор ответа:
0
тангенс в начале*
Похожие вопросы
Предмет: Английский язык,
автор: steshenko19922
Предмет: Русский язык,
автор: Аноним
Предмет: Биология,
автор: 293840
Предмет: Математика,
автор: msefremova1951